Genomic landscape of lymphoepithelioma‐like hepatocellular carcinoma. Issue 2 (18th July 2019) - Chan, Anthony W‐H; Zhang, Zhe; Chong, Charing C‐N; Tin, Edith K‐Y; Chow, Chit; Wong, Nathalie
Abstract: Lymphoepithelioma‐like hepatocellular carcinoma (LEL‐HCC) is a distinct variant of HCC that is characterized by dense tumor‐infiltrating lymphocytes (TILs). Patients with LEL‐HCC also show better clinical outcomes compared to conventional HCC (c‐HCC), which is commonly presented with low TIL. Emerging evidence has begun to highlight tumor‐intrinsic genetic abnormalities in the tumor–host immune interfaces. However, genome‐wide characterization of LEL‐HCC remains largely unexplored. Here, we defined the genomic landscape of 12 LEL‐HCC using whole‐exome sequencing, and further underpinned those genetic alterations related to an immune active microenvironment by comparing findings to 15 c‐HCC that were sequenced in parallel. Overall, the mutational load between LEL‐HCC and c‐HCC was similar. Interestingly, SNV incidences of specific genes ( CTNNB1, AXIN1, NOTCH1, and NOTCH2 ) were significantly higher in c‐HCC than LEL‐HCC, suggesting a plausible link between activated Wnt/β‐catenin and Notch signaling pathways and immune avoidance. Marked focal amplification of chromosome 11q13.3 was prevalent in LEL‐HCC. Using The Cancer Genome Atlas dataset, we further established oncogenes expressed from chromosome 11q13.3 ( CCND1, FGF19, and FGF4 ) to be strongly associated with the immune checkpoint signature ( CD274, PDCD1, BTLA, CTLA4, HAVCR2, IDO1, and LAG3 ). Our results have illustrated for the first time the somatic landscape of LEL‐HCC, and highlighted molecular alterations that could be exploited in combinatory therapy with checkpoint inhibitors in targeting HCC. © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.